Incidence of parental migration in primary school students: an advisory program for psycho-educational specialists (REDEL. Revista Granmense de Desarrollo Local, 2025)
Parental migration represents a social phenomenon of growing impact in the Cuban educational context, especially among primary school students. The study was carried out in the municipality of Cueto, Holguín province, where significant family transformations associated with migratory processes were observed. The article's objective was to present the results of the advisory program, conducted by the Municipality of Cueto's Diagnosis and Guidance Center, which aimed to prepare school psycho-educational specialists to address the impact of parental migration on the learning of primary school students. The program, structured in six sessions, helped strengthen professional competencies, highlight the educational impact of parental migration, and systematize institutional experiences. The results confirmed that the advisory program contributed to improving psycho-educational support in contexts of family vulnerability, positioning the school psycho-educational specialist as a key agent in educational transformation.